Inaccurate offset restoration in total hip arthroplasty results in reduced range of motion - Weber, Markus; Merle, Christian; Renkawitz, Tobias (Scientific reports, 2020)
Offset restoration in total hip arthroplasty (THA) is associated with postoperative range of motion (ROM) and gait kinematics. We aimed to research into the impact of high offset (HO) and standard stems on postoperative ROM. 121 patients received cementless THA through a minimally-invasive anterolateral approach. A 360° hip ROM analysis software calculated impingement-free hip movement based on postoperative 3D-CTs compared to ROM values necessary for activities of daily living (ADL). The same model was then run a second time after changing the stem geometry between standard and HO configuration with the implants in the same position. HO stems showed higher ROM for all directions between 4.6 and 8.9° (p < 0.001) compared with standard stems but with high interindividual variability. In the subgroup with HO stems for intraoperative offset restoration, the increase in ROM was even higher for all ROM directions with values between 6.1 and 14.4° (p < 0.001) compared to offset underrestoration with standard stems. Avoiding offset underrestoration resulted in a higher amount of patients of over 20% for each ROM direction that fulfilled the criteria for ADL (p < 0.001). In contrast, in patients with standard stems for offset restoration ROM did increase but not clinically relevant by offset overcorrection for all directions between 3.1 and 6.1° (p < 0.001). Offset overcorrection by replacing standard with HO stems improved ROM for ADL in a low number of patients below 10% (p > 0.03). Patient-individual restoration of offset is crucial for free ROM in THA. Both over and underrestoration of offset should be avoided.